Why Do Plants Convert Sitosterol to Stigmasterol? - Aboobucker, Siddique I.; Suza, Walter P. (Frontiers in Plant Science, 2019)
A direct role for cholesterol signaling in mammals is clearly established; yet the direct role in signaling for a plant sterol or sterol precursor is unclear. Fluctuations in sitosterol and stigmasterol levels during development and stress conditions suggest their involvement in signaling activities essential for plant development and stress compensation. For instance, sitosterol is implicated in cellulose synthesis and stigmasterol may be involved in gravitropism and tolerance to abiotic stress. The isolation of stigmasterol biosynthesis mutants, offers a promising tool to test the function of sterol end products in signaling responses to developmental and environmental cues.